PSXV-29 Growth and development of bottle-fed white-tailed deer (Odocoileus virginianus) fawns consuming different milk replacers. (7th December 2018) - Stutts, K; Brindza, E; Anderson, M; Stewart, C
Abstract: Common practice for pen-raised white-tailed deer breeders is to bottle-feed fawns that are born as twins or triplets and fawns that are highly valuable in an attempt to increase survivability of these fawns. The objective of this study was to evaluate growth and development of bottle-fed fawns consuming two different commercially-available milk replacers formulated for white-tailed deer. To achieve this, 50 fawns from an established herd were randomly assigned to one of two treatments. Twenty-five fawns received the control milk replacer (33% CP and 30% crude fat), and 25 fawns received the treatment milk replacer (30% CP and 35% crude fat). All fawns were removed from their dams within 24 h after birth and were bottle-fed for an 84-d period according to ranch protocol. In addition to the milk replacer, a commercially-available pelleted feed was provided ad-libitum from d 14 to d 84 of the study. Growth measurements consisting of BW, cannon length, leg length, body length, and heart girth circumference were recorded every 3 wk from d 0 to 84. Data were analyzed using the MIXED procedure of SAS with repeated measures for the effects of time and diet and the time by diet interaction. There was no difference in any of the physical characteristics measured; however, the main effect of treatment did approach significance (P<0.07) for cannon length. Mean cannon length for the control group was 21.4 ± 0.2 cm compared to 20.8 ± 0.3 cm for the treatment group. These data indicate that there is no difference in growth and development as determined by the measurement of BW and the selected physical characteristics of fawns consuming these two commercially-available milk replacers, and either product would be suitable for rearing white-tailed deer fawns in confinement. Key Words: